Simulación multiagente de la actividad humana: una concreción en ergonomía del programa de investigación tecnológico "curso de acción" - Yvon Haradji (Universidade do Porto, 2020)
SMACH (Multi-agent Simulation of Human Activity and Household Consumption) is a simulation platform within EDF's R&D framework. It uses simulation to anticipate and reduce energy consumption at different places of analysis (home, district, town, country). With this paper we aim to explain what the course of action technological research program involves, and to this end we refer to several years of SMACH research. We essentially focus on the importance of the organic relationship between technology and human activity, and we show how this organic relationship evolves over the different stages that this technological research program involves. This paper may be viewed as a basis for generalizing and clarifying the criteria required to validate such a program and as a contribution towards reflection on design in ergonomics.